Kekerasan Budaya Pasca 1965 dalam Novel Pulang dan Dari Dalam Kubur - Hanifah, Aufa; Robertus Robet (Saskara : Indonesian Journal of Society Studies, 2022)
This study aims to describe cultural violence depicted in novels Dari dalam Kubur (2020) and Pulang (2013), both novels describe the post-1965 mass massacres in Indonesia. This study uses a qualitative approach with the method of Critical Discourse Analysis. Data collection was carried out by means of a literature study. This research is based on Johan Galtung's concept of cultural violence and Pierre Bourdieu's symbolic violence. The results showed that in both novels there was personal violence and structural violence. To legitimize these two violences, the New Order government used cultural aspects such as ideology, religion, language, art and knowledge. This is the same as the symbolic principle in Pierre Bourdieu's idea of ​​symbolic violence or invisible violence. The use of these cultural aspects has the function of changing the moral and ideological values ​​of the people so that they consider violence against communists and ethnic Chinese community to be normal, and even must be done.